ALISHER NAVOIY ABOUT THE DEVELOPMENT OF SOCIETY AND HUMAN FACTOR (Scientific journal of the Fergana State University, 2023)
This article deals with the relationship between the individual and society, a fair system of democratic principles, which are reflected in the works of the great poet and thinker Alisher Navoi.